2009
DOI: 10.1017/s1092852900000225
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making and Prepotent Response Inhibition Functions in Excessive Internet Users

Abstract: Introduction: Excessive Internet use (EIU), also described as Internet addiction or pathological Internet use, has already become a serious social problem around the world. Some researchers consider EIU as a kind of behavioral addiction. However, there are few experimental studies on the cognitive functions of excessive Internet users (EIUers) and limited data are available to compare EIU with other addictive behaviors, such as drug abuse and pathological gambling.Methods: In this study, we examined EIUers' fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 39 publications
7
90
0
8
Order By: Relevance
“…In a study made with adolescents in China, a significant positive correlation was found between IA scores and impulsivity and attention scores (19). In the literature, ADHD is often characterized by increased reward sensitivity, getting bored easily (45), preference for fast changing and quickly response-producing stimuli, orientation towards smaller, short-term rewards rather than long-term rewards, impulsivity (19) and disinhibition (46). It has been suggested that these characteristics are sufficiently catered to by internet use or that self-control deficits intrinsic to ADHD may increase the predisposition for IA (17,45).…”
Section: Discussionmentioning
confidence: 99%
“…In a study made with adolescents in China, a significant positive correlation was found between IA scores and impulsivity and attention scores (19). In the literature, ADHD is often characterized by increased reward sensitivity, getting bored easily (45), preference for fast changing and quickly response-producing stimuli, orientation towards smaller, short-term rewards rather than long-term rewards, impulsivity (19) and disinhibition (46). It has been suggested that these characteristics are sufficiently catered to by internet use or that self-control deficits intrinsic to ADHD may increase the predisposition for IA (17,45).…”
Section: Discussionmentioning
confidence: 99%
“…A study using the Iowa Gambling Task found that Internet-addicted individuals have deficits in decision-making function, chiefly a strategy learning lag rather than an inability to learn from task contingencies. They showed better performance on a Go/no-go task, suggesting some dissociation between mechanisms of decisionmaking and those of prepotent response inhibition (55).…”
Section: Cognitive Factors Associated With Problematic Internet Usementioning
confidence: 94%
“…Indeed, several studies have shown deficits in inhibitory control in other types of addictions such as substance use disorder [39] and pathological gambling [40]. In this vein, Cao et al, [32] and Sun et al, [41] have compared the performance of Internet addicts (based on the diagnostic criteria proposed by Young) and control participants on prepotent response inhibition. Surprisingly, Cao et al, [32] found Internet addicts to have a lower ability to inhibit a prepotent response than control participants, whereas Sun et al, [41] obtained the opposite result, namely better inhibition performance for the Internet addiction group than for the control participant group.…”
Section: Problematic Internet Use and Controlled Aspects Of Self-regumentioning
confidence: 99%
“…In this vein, Cao et al, [32] and Sun et al, [41] have compared the performance of Internet addicts (based on the diagnostic criteria proposed by Young) and control participants on prepotent response inhibition. Surprisingly, Cao et al, [32] found Internet addicts to have a lower ability to inhibit a prepotent response than control participants, whereas Sun et al, [41] obtained the opposite result, namely better inhibition performance for the Internet addiction group than for the control participant group. These contradictory results could possibly be attributed to the fact that the two studies did not use the same laboratory task to assess prepotent response inhibition.…”
Section: Problematic Internet Use and Controlled Aspects Of Self-regumentioning
confidence: 99%
See 1 more Smart Citation